Welfare effects of investment incentive policies: A quantitative assessment - Hans Fehr (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1995)
This paper deals with the intergenerational incidence of corporate tax policies in the overlapping generation model. Corportate tax reforms affect the welfare levels of individuals via three Channels: (i) changes in the net. tax burdens, (ii) changes in the factor prices, and (iii) changes in deadweight loss associated with the taxes. We develop formulas to isolate t.hese effects in a closed and a smal] open economy and then apply these formulas to a policy experiment, similar to a recent German corporate tax reform plan. The simulations suggest that generations' utility changes are mainly due to intergenerational income effects. While in closed economies changes in net tax burdens are most important especially in the short-run, the revaluation of the initial capital stock is an important redistribution Channel in the smail open economy.
Keywords: C68; H22; 330; Dynamic CGE modelling; Investment incentives; intergenerational tax incidence; equal yield tax reform